Toxicological evaluation of insecticides to control the first instar larvae of Phthorimaea operculella in tobacco culture - Almeida, Armando Antunes de; Carneiro, Maurízia de Fátima (Pesquisa Agropecuaria Brasileira, 2014)
Leaves of 'Amarelinho' tobacco (Nicotiana tabacum L.) were sprayed with different concentrations of six insecticides. After drying the leaves, first instar larvae of Phthorimaea operculella were placed on the leaves, and countings were made after certain times of exposition, and deaths were registered. At third hour of exposition a relationship between logarithm of the insecticide concentration and larval mortality, for each insecticide, was determined; lethal concentrations at 50% (CL50) were, also, determined. After 24 hours of exposition Karphos presented 100% of larval mortality for all concentrations used; also Orthene, Thiobel and Nuvacron have presented 100% but only for higher concentrations; Dimethoate and Sevin did not reach 100% of larval mortality in any of the concentrations used.
Keywords: Nicotiana tabacum; Lepidoptera; larval mortality